Being part of history, being part of activism: Exploring the lives and experiences of Black people with learning disabilities. (13th March 2022) - Christian, Paul; Ledger, Sue
Abstract: My name is Paul Christian. I am a Black British man with learning disabilities. The lives and experiences of Black people with learning disabilities are under ‐ represented in the UK history of learning disability. This article explains my involvement in activism to change this and shares the learning from these projects. It discusses the process of co‐writing and why research is needed to record and share the experiences of Black people admitted to the former institutions and the importance of accessible information about Black history, race and racism. Accessible summary: My name is Paul Christian. I am a Black British man with learning disabilities. We do not know much about the lives of Black British people with learning disabilities in the past. This article explains work I have begun to change this. It describes three pieces of activism in support of the Black Lives Matter movement. It shares learning from these projects and ideas for next steps. It tells the story of how I met Sue my co‐author and explains how we wrote this article together. This study is important because it shows more research is needed to understand the experiences of Black people admitted to long stay institutions. It demonstrates how people with learning disabilities are coming together to learn and talk about Black British history, discrimination and race, and to take action to stop racism. It encourages people interested in co‐writing to try it out.